On the Identification of Vertices Using Cycles - Rosendahl, Petri (The Electronic Journal of Combinatorics, 2003)
A set of cycles C_1,… ,C_k in a graph G is said to identify the vertices v if the sets {j:vC_j} are all nonempty and different. In this paper, bounds for the minimum possible k are given when G is the graph Z_p^n endowed with the Lee or Hamming metric or G is a complete bipartite graph.